The Administration of Ketorolac in Reducing the Degree of Peritoneal Adhesion among Post Laparotomic Patients - Arlan, M. Alsen; Tri Hanggono Acmad, Ponpon S Idjradinata, Suwandi Sugandi, (Opción, 1970)
The formation of permanent adhesion depends on the balance between pro-inflammatory and anti-inflammatory processes in which can be regulated through the admission of ketorolac. This study was conducted to obtain knowledge about the relationship between the administration of ketorolac and the degree of peritoneal adhesion in patients underwent laparotomy surgery. Comparative experimental case study by treating two groups that had been randomly selected by using randomized controlled trial method. Patients treated with ketorolac have a significant reduction in peritoneal adhesion occurrence with the mean value of adhesion score of 3.0333 as compared to the control group.